Economic Literacy and Human Development through Technology-Based Economic Education for Generation Z Students - Nanda Rezky Pratama; Wahyu; Riya Rahmadani (Department of Economics Education, Faculty of Economics, Universitas Negeri Makassar, 2024)
Economic literacy and human development are two fundamental aspects in the effort to create a prosperous and competitive society. This study aims to explore the influence of economic literacy on human development through technology-based economic education for Generation Z students. Using a qualitative approach with a case study design, 43 students from the Faculty of Economics and Business at Universitas Negeri Makassar participated in this research. Data were collected through in-depth interviews and analyzed using a thematic analysis approach. The findings revealed that while most students possess a good basic understanding of economic concepts, challenges remain in applying these concepts to real-life situations. Technology in education has proven instrumental in enhancing economic understanding through tools like market simulations and e-learning platforms. However, key obstacles include unequal technological infrastructure, particularly in remote areas, and limited teacher competence in effectively integrating technology into the curriculum. Addressing these challenges is essential to ensure that economic literacy can significantly contribute to human development and the competitiveness of Generation Z in the future.